Involvement of Husbands in Maternal Care: Impact on Postpartum Blues – A Systematic Review - Nurfatimah, Nurfatimah; Sumiaty, Sumiaty; Sulistiani, Ita; Basrowi, Ray Wagiu; Novitasari, Prihatini Dini; Ramadhan, Kadar (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Postpartum blues is a common emotional condition affecting mothers after childbirth, with a global prevalence of approximately 39.0%. This condition arises from an interplay of biological, psychological, and social influences, including hormonal fluctuations and psychosocial stressors such as role transition and sleep deprivation. Consistent emotional and practical support from partners and family members helps buffer these stressors. This systematic review aimed to explore the specific role of husbands in preventing postpartum blues by examining various forms of their involvement during pregnancy, labor, breastfeeding, and postpartum care. Following PRISMA guidelines, relevant English-language studies published between 2019 and 2024 were systematically identified from PubMed, ScienceDirect, and Google Scholar. After independent screening of 3,073 initial records by two reviewers and subsequent exclusions, 11 new studies were included for synthesis. The findings highlight that husband involvement in prenatal care significantly reduces the incidence of postpartum blues , and participation in digital mental health interventions enhances emotional support for women experiencing postpartum depression. Perceived husband support consistently correlates with improved emotional well-being and quality of life, extending beyond immediate emotional assistance to impact overall maternal QoL. Other factors like maternal age, education, parity, and broader family support also influence postpartum blues symptoms. This review underscores that active and consistent husband involvement is crucial for mitigating postpartum emotional challenges and improving maternal well-being, advocating for its integration into maternal health programs.